Imatinib treatment attenuates growth and inflammation of angiotensin II induced abdominal aortic aneurysm. (June 2016) - Vorkapic, Emina; Dugic, Elma; Vikingsson, Svante; Roy, Joy; Mäyränpää, Mikko I.; Eriksson, Per; Wågsäter, Dick
Abstract: Background: Abdominal aortic aneurysm (AAA) is characterized by vascular remodeling with increased infiltration of inflammatory cells and apoptosis/modulation of vascular smooth muscle cells (SMCs). Imatinib is a selective inhibitor of several tyrosine kinases, including PDGF receptors, Abl, and c-kit. The objective of this study was to characterize the potential protective role of imatinib on AAA development and the molecular mechanisms involved. Methods: Male ApoE −/− mice were infused with angiotensin (Ang) II (1000 ng/kg/min) for 4 weeks to induce AAA or saline as controls. Daily treatment with 10 mg/kg imatinib, or tap water as control, was provided via gavage for 4 weeks. Results: Treatment with imatinib was found to decrease the aortic diameter and vessel wall thickness, mediated by multiple effects. Imatinib treatment in AngII infused mice resulted in a reduced cellular infiltration of CD3ε positive T lymphocytes by 86% and reduced gene expression of mast cell chymase by 50% compared with AngII infused mice lacking imatinib. Gene expression analysis of SMC marker SM22α demonstrated an increase by 48% together with a more intact medial layer after treatment with imatinib as evaluated with SM22α immunostaining. Conclusion: Present findings highlight the importance of tyrosine kinase pathways in the development of AAA. Our results show, that imatinib treatment inhibits essential mast cell, T lymphocyte and SMC mediated processes in experimental AAA. Thus, our results support the idea that tyrosine kinase inhibitors may be useful in the treatment of pathological vascular inflammation and remodeling in conditions like AAA. Highlights: Imatinib attenuates AngII-induced AAA formation and growth. Imatinib plays a part in preventing pathological vascular inflammation. Imatinib treated mice displayed a more intact medial layer of SMC and vessel wall morphology. Blockage of tyrosine kinase signaling using imatinib may be extended as treatment of AAA.